SHEAR BUCKLING ANALYSIS OF CORRUGATED WEB I-GIRDER WITH 3D NONLINEAR FINITE ELEMENT METHOD - Ni Putu Ary Yuliadewi; Heppy Kristijanto; Bambang Piscesa; Priyo Suprobo; Faimun Faimun (Journal of Civil Engineering, 2021)
This paper presents a shear buckling analysis of corrugated web I-girder beam using nonlinear finite element analysis. An in-house finite element package called 3D-NLFEA is used in the simulation. The steel material is modelled as solid elements with one-eight aspect ratio between the element size and its thickness. The double sine waves equation is used to generate the initial imperfection in the corrugated web. The nonlinear geometry deformation, which is essential in capturing the buckling behavior, is considered using the 2nd order analysis in 3D-NLFEA. A comparison with the carried out experimental test in the laboratory showed that the peak prediction from the analytical model was in good agreement. Furthermore, using the double sine waves equation as the initial imperfection can closely predict the buckling mode and shapes of the corrugated web I-girder as obtained from the experimental test.